2017
DOI: 10.1155/2017/6254793
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Drying as a Quick Preparation Method for Dried Tangerine Peel

Abstract: To establish the most convenient and effective method to dry tangerine peels, different methods (sun drying, hot-air drying, freeze drying, vacuum drying, and medium- and short-wave infrared drying) were exploited. Our results indicated that medium- and short-wave infrared drying was the best method to preserve nutraceutical components; for example, vitamin C was raised to 6.77 mg/g (D.W.) from 3.39 mg/g (sun drying). Moreover, the drying time can be shortened above 96% compared with sun drying. Importantly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The data of the Food and Agriculture Organization of the United Nations have shown that China is the world's largest producer of tangerine with a surface area of 1.34 million ha and a production of 19.21 million metric tons in 2018 [ 11 ]. This fruit is largely consumed fresh for its distinctive bittersweet characteristic flavour and its high nutritional contents [ 38 , 39 ]. Furthermore, about 28 % of total tangerine fruit is processed to produce juice and other commercial products [ 40 ].…”
Section: World Production Of Tangerine Pomegranate and Banana Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of the Food and Agriculture Organization of the United Nations have shown that China is the world's largest producer of tangerine with a surface area of 1.34 million ha and a production of 19.21 million metric tons in 2018 [ 11 ]. This fruit is largely consumed fresh for its distinctive bittersweet characteristic flavour and its high nutritional contents [ 38 , 39 ]. Furthermore, about 28 % of total tangerine fruit is processed to produce juice and other commercial products [ 40 ].…”
Section: World Production Of Tangerine Pomegranate and Banana Fruitsmentioning
confidence: 99%
“…The tangerine is one of the most popular and most accepted fruits worldwide, this fruit is composed of the peel, arils and seeds ( Table 1 ) . Tangerine is very rich in nutritional content, especially fibres, carbohydrates, lipids, proteins, oligo-elements such as calcium (Ca), iron (Fe), manganese (Mn), phosphorus (P), potassium (K), copper (Cu), sodium (Na) and zinc (Zn), fatty acids [ 6 , 39 , 72 ] and also contains bioactive compounds, such as antioxidants, flavonoids, vitamins (Vitamins C, A, E, K, B 1 , B 2 , B 3 , B 5 ) and other phenolic acids [ 73 ].…”
Section: Tpw Ppw and Bpw Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, isoleucine 7, threonine (8), arginine (9), and glutamine (10), labeled with asterisks in Figure 2A, were newly generated amino acids during the full sun-drying processing, as they were identified exclusively in Ganpu tea, but not in Pu-erh raw tea or mandarin peel. In addition to the common tea catechins, such as GC 11 (26) were newly generated during the sun-drying process, as they were discovered exclusively in Ganpu tea ( Figure 2B).…”
Section: Analysis Of Flavor Substances From Ganpu Teamentioning
confidence: 99%
“…To date, numerous methods including hot-air drying, freeze drying, vacuum drying, and infrared drying, have been applied to dry agricultural products (7)(8)(9). Hot-air drying is the method most commonly used to dry Ganpu tea.…”
Section: Introductionmentioning
confidence: 99%